Language retention based on local wisdom: anthropological and linguistic perspectives - Musa Hefer Smas; Endang Nurhayati; Margana Margana (PT. Anagata Sembagi Education, 2025)
This study examines the strategy of local language retention based on local wisdom with an interdisciplinary approach, namely anthropology and Linguistics. The phenomenon of language shift that occurs in various regions in Indonesia is a serious threat to the continuity of regional languages as cultural identities. Globalization, urbanization, and the development of Information Technology also accelerate the process of language assimilation, thereby reducing the use of local languages, especially among the younger generation. Through a qualitative ethnographic approach, this study describes in depth how the practice of language inheritance takes place in the family, community, education, and media environment. Data were obtained through participatory observation, in-depth interviews with community leaders, parents, children, and schools, as well as documentation of language interactions in everyday life. The results showed that the sustainability of the local language is strongly influenced by the active role of the family, community support, integration in the school curriculum, as well as the use of digital media for documentation and dissemination of language. This study emphasizes the importance of cross-generational engagement in preserving local languages, as well as the need for cultural policies that support the revitalization of regional languages through a culture-based and participatory approach. Thus, the preservation of the local language is not only a linguistic effort, but also as part of the preservation of the nation's cultural identity.